A relationship between phages and organic carbon in wastewater treatment plant effluents. (1st August 2022) - Modin, Oskar; Fuad, Nafis; Abadikhah, Marie; I'Ons, David; Ossiansson, Elin; Gustavsson, David J.I.; Edefell, Ellen; Suarez, Carolina; Persson, Frank; Wilén, Britt-Marie
Highlights: Virus-like particles (VLPs) related to wastewater treatment plant effluent quality. VLP concentrations vary between wastewater treatment plants. Effects of tertiary treatment on VLP concentrations varied. Phage community composition differed between treatment plants. Phage-host associations showed several connections to Comamonadaceae . Abstract: With stringent effluent requirements and the implementation of new processes for micropollutant removal, it is increasingly important for wastewater treatment plants (WWTPs) to understand the factors affecting effluent quality. Phages (viruses infecting prokaryotes) are abundant in the biological treatment processes. They can contribute to organic carbon in the treated effluent both because they are organic in nature and occur in the effluent and because they cause lysis of microorganisms. Today very little is known about the effects of phages on effluent quality. The goal of this study was, therefore, to determine the relationship between phages and organic carbon in WWTP effluents. We also examined the diversity, taxonomy, and host-association of DNA phages using metagenomics. Effluent samples were collected from four WWTPs treating municipal wastewater. Significant differences in both organic carbon and virus-like particle concentrations were observed between the plants and there was a linear relationship between the two parameters. The phage communities were diverse with many members being taxonomically unclassified. Putative hosts were dominated by bacteria known to be abundant in activated sludge systems such as Comamonadaceae . The composition of phages differed between the WWTPs, suggesting that local conditions shape the communities. Overall, our findings suggest that the abundance and composition of phages are related to effluent quality. Thus, there is a need for further research clarifying the association between phage dynamics and WWTP function.